Tracing the traces of doxa: Socialization and internalization in Kampung Pentigraf Indonesia - Harendika, Melania Shinta; Salam, Aprinus; Sudibyo, Sudibyo (Universitas Dian Nuswantoro, 2025)
This study scrutinizes the personal and collective doxa in Kampung Pentigraf Indonesia (The Indonesian Pentigraf Village or KPI), a community started by Tengsoe Tjahjono. This study applies Bourdieu’s theory of the field of cultural production as the frame to observe how Tjahjono’s personal beliefs, or personal doxa, are spread to the members of KPI and hence converted as collective doxa. This study uncovers how Tjahjono’s values shape the community dynamics by exploring socialization and internalization practices in KPI. The findings show that the personal doxa rooted in Tjahjono’s symbolic capital reinforces social structures in KPI, where his power drives the community’s practices. This study emphasizes the role of social sanctions in preserving the community’s principles to guarantee that the Pentigrafs written by the KPI members obey the rules. Moreover, the study discovers how vertical and horizontal interactions in the community contribute to social reproduction, allowing KPI standards to be passed down to new members. This study contributes to understanding how literary communities play a role in cultural production, proposing insights into the dynamics of symbolic power and the practices of socialization and internalization in a minor but highly organized creative setting.